Preliminary Investigation of Zooplankton from Mankara lake, Aamgaon Mahal dist. Gadchiroli (M.S), India. (International Journal of Food and Nutritional Sciences, 2023)
This study presents a preliminary investigation of the zooplankton community in Mankara lake, Aamgaon Mahal District, Gadchiroli. We examined the diversity, abundance, and ecological significance of zooplankton across three selected stations (ML-1, ML-2, and ML-3) during different seasons. A total 13 zooplankton species were identified, belonging to rotifers, cladocerans, and copepods. The abundance of zooplankton varied seasonally and spatially, with [station/season] showing the highest density. Our findings provide insights into the zooplankton community in Mankara lake and highlight the importance of understanding the ecological dynamics of freshwater ecosystems. This study contributes to the conservation and management efforts of Mankara lake and similar freshwater resources.